HUBUNGAN PEMBERIAN IMUNISASI DASAR DENGAN TUMBUH KEMBANG ANAK USIA 9-24 BULAN DI PUSKESMAS MERDEKA PALEMBANG - kurniawaty, kurniawaty (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Imunization is an attempt to cause or boost a person's immune actively to a disease, so that if one day exposed to the disease. The purpose of this research is to analyze the relationship between the provision of primary immunization with child growth and development aged 9-24 months in Puskesmas Merdeka. The method in this research is analytical survey with cross sectional approach. Population in this research is mothers who have infants aged 9-24 months, with total sample of 35 respondents. The results showed that of 24 babies who received complete basic immunization and had good growth as many as 23 babies (82,1%). Based on the result of Chi-square statistic test on significance level α = 0,05 got p value = 0.002 ≤ α = 0,05, there is relation of Basic Immunization Giving with Growth of 9-24 months old child. The results showed that of 24 babies who received complete basic immunization and had good development as many as 17 babies (94.4%). Based on Chi-square statistical test at significance level α = 0.05 in p value = 0.002 ≤ α = 0, 05 hence there is a relation between giving immunization with the development of child age 9-24 month. The result of this research can give input for health worker in increasing the coverage of basic immunization so as to prevent the happening of disease that can growth and development of child. Keywords: Provision of primary immunization, Development, Growth